California's Frontier Naturalists - Beidleman, Richard G. (Book collections on Project MUSE., 2006)
This book chronicles the fascinating story of the enthusiastic, stalwart, and talented naturalists who were drawn to California's spectacular natural bounty over the decades from 1786, when the La Prouse Expedition arrived at Monterey, to the Death Valley expedition in 1890-91, the proclaimed "end" of the American frontier. Richard G. Beidleman's engaging and marvelously detailed narrative describes these botanists, zoologists, geologists, paleontologists, astronomers, and ethnologists as they camped under stars and faced blizzards, made discoveries and amassed collections, kept journals and